Spintronic Functionality of BiFeO3 Domain Walls. (23rd September 2014) - Lee, Ji Hye; Fina, Ignasi; Marti, Xavi; Kim, Young Heon; Hesse, Dietrich; Alexe, Marin
<x xml:space="preserve">Abstract</x> Anisotropic magnetoresistance at the BiFeO3 domain walls has been observed thanks to the realization of micro‐devices that allow the direct magneto‐transport characterization of the domain‐walls. Anisotropic magnetoresistance of ferromagnetic metals has been a pillar in spintronic technology, and now it is evidenced at the conductive domain walls of an insulating ferroelectric material, which implies that domain walls become an electrically tunable nanospintronic object. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>